2013
DOI: 10.1097/jom.0000000000000030
|View full text |Cite
|
Sign up to set email alerts
|

Do Zero-Cost Workers' Compensation Medical Claims Really Have Zero Costs? The Impact of Workplace Injury on Group Health Insurance Utilization and Costs

Abstract: Objective Previous research suggests that non–workers’ compensation (WC) insurance systems, such as group health insurance (GHI), Medicare, or Medicaid, at least partially cover work-related injury and illness costs. This study further examined GHI utilization and costs. Methods Using two-part model, we compared those outcomes immediately after injuries for which accepted WC medical claims made zero or positive medical payments. Results Controlling for pre-injury GHI utilization and costs and other covaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
(29 reference statements)
1
5
0
Order By: Relevance
“…Our results were qualitatively similar to the results from Afsaw, Rosa, and Mao (20) but our odds ratios and estimated expenditures were higher than the results from Bhattacharya and Park, although they looked only at one month post-injury rather than three (18). We evaluated only patient care workers, a group with higher than average injury rates and presumably good access to care and were able to capture a wide array of injuries including those without worker’s compensation claims.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results were qualitatively similar to the results from Afsaw, Rosa, and Mao (20) but our odds ratios and estimated expenditures were higher than the results from Bhattacharya and Park, although they looked only at one month post-injury rather than three (18). We evaluated only patient care workers, a group with higher than average injury rates and presumably good access to care and were able to capture a wide array of injuries including those without worker’s compensation claims.…”
Section: Discussionsupporting
confidence: 87%
“…Afsaw, Rosa, and Mao (20) also used Thomson Reuters MarketScan data to determine whether group health insurance at least partially covered work-related injury costs. Controlling for pre-injury group health insurance cost, they found increased group health insurance utilization and costs regardless of the value of workers’ compensation medical claims; increases were higher for zero-cost workers’ compensation claims than for positive workers’ compensation claims.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the medical costs of work-related injuries might not be covered by workers’ compensation programs if adjudication determines the injury is not work-related. 27 If claimants need to delay medical treatment after a claim has been filed, the medical costs are likely to be paid by other payers or the injured workers themselves. Several studies have reported a significant portion of work-related injuries that were assigned zero-cost workers’ compensation medical claims due to delayed care.…”
Section: Discussionmentioning
confidence: 99%
“…For example, 15.9% of workers’ compensation claimants had zero-cost medical claims in an analysis of administrative data of 16 employers across the United States. 27 Other studies have also reported the issue of zero-cost workers’ compensation medical claims. 2833 The zero-cost workers’ compensation medical claims are commonly seen in less-acute injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple long-term studies of unionized Washington State carpenters and drywallers have found evidence of cost-shifting from WC to HI for back, upper extremity, and knee disorders (Lipscomb, Dement, Silverstein, Cameron, et al, 2009; Lipscomb et al, 2015; Schoenfisch et al, 2014). Several studies have found associations between occupational injury and subsequent increases in HI expenditures (Asfaw, Rosa, & Mao, 2013; Williams et al, 2017). Expanded HI coverage (via the Affordable Care Act [ACA] or Massachusetts health care reform) was associated with 5% to 10% decreases in hospital and emergency department WC billing volume (Armour, Goutam, & Heaton, 2016; Bronchetti & McInerney, 2017; Heaton, 2012), and conversely, a 10 percentage point decrease in HI coverage was associated with a 15% increase in Texas WC bills (Dillender, 2015), suggesting that broader access to HI may lower WC costs via cost-shifting mechanisms.…”
Section: Research On Coverage Gaps and Cost-shiftingmentioning
confidence: 99%